Authentication of Edible Bird's Nest (EBN) and its adulterants by integration of shotgun proteomics and scheduled multiple reaction monitoring (MRM) based on tandem mass spectrometry. (November 2019) - Ma, Xueting; Zhang, Jiukai; Liang, Jinzhong; Ma, Xiuli; Xing, Ranran; Han, Jianxun; Guo, Lihai; Chen, Ying
Abstract: Edible bird's nest (EBN) has been traditionally regarded as a kind of medicinal and healthy food in Asia. However, economically motivated adulteration (EMA) has been an issue in the EBN supply chain. To develop an accurate high-throughput approach for detecting EBN and its adulterants (exemplified by porcine skin, swim bladder, white fungus, and egg white), shotgun proteomics was applied for discovery of specific peptides that were subsequently converted into scheduled multiple reaction monitoring (MRM) transitions. Totally, 28 specific peptides were verified as unique to EBN and its adulterants by tandem mass spectrometry. Subsequently, 9 quantitative MRM-transitions of peptides from adulterants and 2 internal standard references from EBN were screened for the quantitative analysis of the adulterants, which allowed detection of adulterants in EBN matrix in the range of 1–80%. These results suggested that integration of shotgun proteomics and scheduled MRM had potential for the authentication of EBN and its adulterants. Graphical abstract: Unlabelled Image Highlights: A Proteomics method was reported for authentication of edible bird's nest. 28 specific peptides were discovered as unique to edible bird's nest or its 4 common adulterants by shotgun proteomics. 11 quantitative MRM-transitions of peptides were screened for quantitation of adulterants by scheduled MRM. Characteristics of quantitative MRM-transitions were described. An optimal workflow of discovering specific peptide markers of protein-containing food was proposed.